Assessment of the thrombin generation assay in haemophilia: Comparative study between fresh and frozen platelet‐rich plasma. (23rd November 2012) - Vila, V.; Aznar, J. A.; Moret, A.; Marco, A.; Navarro, S.; Vila, C.; España, F.
Summary The severity of haemophilia A has traditionally been classified by the dosage of factor VIII (FVIII) by one‐step coagulation tests. However, an homogeneous group of patients with similar FVIII levels show clinical heterogeneity and 10–15% of the patients classified as severe haemophilia do not have a severe bleeding phenotype. Traditional tests used for measuring FVIII are not capable of detecting other prohaemorrhagic or prothrombotic factors. Global tests as the thrombin generation assay (TGA) may detect these haemostatic factors. So TGA may be an additional tool for classifying the actual severity of haemophilia. Our group is carrying out correlation tests between FVIII and TGA in platelet‐poor and ‐rich plasmas (PPP and PRP, respectively). PRP has the inconvenience that must be done freshly soon after blood extraction. Our aim is to study the differences between TGA performed with fresh and frozen PRP and PPP and its implementation in multicenter studies. We included 70 patients with severe haemophilia A in prophylactic treatment. Venous blood drawing was obtained prior to administration of FVIII, at the trough levels. FVIII measurement and TGA were performed in fresh and frozen PRP and PPP. The platelet absence caused a significant decrease in TGA although PPP and PRP correlated well. Frozen samples gave different results in PPP, but there were no significant differences between fresh and frozen PRP. This fact enables using frozen PRP in multicenter studies with a TGA‐specialized laboratory for reclassifying haemophilia severity and for pharmacokinetic studies with TGA.